Estimation of production cross-sections, transmutation and gas generation from radionuclides (A ∼50–60) in fusion environment. (June 2022) - Pandey, Jyoti; Pandey, Bhawna; Subhash, P.V.; Kanth, Priti; Rajput, M.; Vala, S.; Makwana, Rajnikant; Suryanarayana, S.V.; Agrawal, H.M.
Abstract: Degradation of material properties under neutron irradiation generates a requirement for studying effects on materials in a fusion environment and optimizing radiation-resistant materials for future applications. In the present work, the durability of stainless steel (SS) alloy used in ITER-like fusion devices is studied. We have predicted the amount of radionuclides produced in the material upon neutron irradiation at various locations is determined using the ACTYS, neutron activation code, for a typical one-dimensional geometry of ITER-like fusion reactor. The ACTYS code is further used to determine the gas production from 55 Fe, 59 Ni, and other long-lived radionuclides in the material. To further stress the importance of gas production in fusion materials, a comparative study of gas production cross-sections as given in various standard data libraries is examined using TALYS-1.8 and is presented in the paper. Highlights: In the present work, our main aim is to highlight the importance of long lived radionuclides produced inside the fusion reactor environment after neutron irradiation from D-T plasma. The various radionuclides will be formed through different pathways. These radionuclides will produce more problems in the damage. Neutron induced reaction on radionuclides enhance the gaseous level of hydrogen and helium gases. Transmutation also leads to the production of gas molecules like hydrogen (H) and helium (He) through (n, p) and (n, α) reaction channels. In the present work, the durability of stainless steel (SS316L(N)-IG) alloy used in ITER-like fusion devices is studied. For one dimensional geometry of ITER like reactor, the amount of radionuclides produced in the material upon neutron irradiation at various locations is determined using ACTYS, neutron activation code. ACTYS is further used to determine gas production from 55 Fe, 59 Ni and other long-lived radionuclides in the material. To further stress the importance of gas production in fusion materials, a comparative study of gas production cross-sections as given in various standard data libraries are examined using TALYS-1.8 and is presented in the paper. The amount of hydrogen, helium produced due to each radionuclides in Ã50–60 is also calculated.